SAFE‐HEaRt: Rationale and Design of a Pilot Study Investigating Cardiac Safety of HER2 Targeted Therapy in Patients with HER2‐Positive Breast Cancer and Reduced Left Ventricular Function. (17th March 2017) - Lynce, Filipa; Barac, Ana; Tan, Ming T.; Asch, Federico M.; Smith, Karen L.; Dang, Chau; Isaacs, Claudine; Swain, Sandra M.
Abstract : Background: Human epidermal growth receptor 2 (HER2) targeted therapies have survival benefit in adjuvant and metastatic HER2 positive breast cancer but are associated with cardiac dysfunction. Current U.S. Food and Drug Administration recommendations limit the use of HER2 targeted agents to patients with normal left ventricular (LV) systolic function. Methods: The objective of the SAFE‐HEaRt study is to evaluate the cardiac safety of HER2 targeted therapy in patients with HER2 positive breast cancer and mildly reduced left ventricular ejection fraction (LVEF) with optimized cardiac therapy. Thirty patients with histologically confirmed HER2 positive breast cancer (stage I–IV) and reduced LVEF (40% to 49%) who plan to receive HER2 targeted therapy for ≥3 months will be enrolled. Prior to initiation on study, optimization of heart function with beta‐blockers and angiotensin converting enzyme inhibitors will be initiated. Patients will be followed by serial echocardiograms and cardiac visits during and 6 months after completion of HER2 targeted therapy. Myocardial strain and blood biomarkers, including cardiac troponin I and high‐sensitivity cardiac troponin T, will be examined at baseline and during the study. Discussion: LV dysfunction in patients with breast cancer poses cardiac and oncological challenges and limits the use of HER2 targeted therapies and its oncological benefits. Strategies to prevent cardiac dysfunction associated with HER2 targeted therapy have been limited to patients with normal LVEF, thus excluding patients who may receive the highest benefit from those strategies. SAFE‐HEaRt is the first prospective pilot study of HER2 targeted therapies in patients with reduced LV function while on optimized cardiac treatment that can provide the basis for clinical practice changes. Abstract : The SAFE‐HEaRt study tests the hypothesis that HER2 targeted therapies may be safely used in patients with mildly decreased left ventricular ejection fraction with appropriate cardiac monitoring and treatment. This is the first prospective evaluation of HER2 targeted therapy in patients with HER2 positive breast cancer and decreased cardiac function, a group of patients who at present have limited treatment options and therefore are at risk for worse oncologic outcomes.